2013
DOI: 10.1108/el-08-2011-0127
|View full text |Cite
|
Sign up to set email alerts
|

Reading strategy and the need of e‐book features

Abstract: Purpose-The purpose of this paper is to explore college students' use of electronic reading strategies in reading e-books and the features provided by e-book systems. Both academic reading and leisure reading are evaluated from students' responses. Design/methodology/approach-Both qualitative and quantitative data are collected. In total, eight college students volunteered for in-depth interview to express their strategy in reading e-books. Reading strategies employed by college students are summarized. A set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This indicated that adolescents conducted digital social reading mainly to kill time and to seek self-improvement, which is exactly the same as people do in traditional reading. In this sense, the current digital social reading carries the same fundamental function of reading: enjoyment and utility (ChanLin, 2013;Greanye and Neuman, 1990).…”
Section: Relationship Between Social Reading Motivation and Behaviourmentioning
confidence: 99%
“…This indicated that adolescents conducted digital social reading mainly to kill time and to seek self-improvement, which is exactly the same as people do in traditional reading. In this sense, the current digital social reading carries the same fundamental function of reading: enjoyment and utility (ChanLin, 2013;Greanye and Neuman, 1990).…”
Section: Relationship Between Social Reading Motivation and Behaviourmentioning
confidence: 99%
“… The experiment is confined to academic use only. In addition to evaluating the use case within the academic social environment, this design aspect acknowledges the studies by ChanLin (2013) , Brook et al. (2010), Delgado et al.…”
Section: Methodsmentioning
confidence: 99%
“…Foertsch (1998) describes reading as follows: “The process involves intellectual and complex tasks that may encompass the use of several cognitive strategies for achieving specific objectives”. In a student study by ChanLin (2013) titled “Reading strategy and the need of e-book features”, interviews were used to structure hypotheses that were then tested through think-aloud protocols, surveys and statistical analysis. The findings confirmed that students read in different patterns to a leisure reader when using e-books, and study participants demonstrated pre-reading text subconsciously and focusing on selections of interest when performing academic reading.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of interactive reading activity, readers are required to have a complex process of comprehension, a great variety of reading skills, and a high level of cognitive engagement. Organizations or tools that possess the characteristics of social reading include: offline reading clubs, library reading salons, online reading community, interactive e-books, collaborative annotation systems, reading activities based on social network software, and so on (Chen, 2013;Chanlin, 2013;Kelly, Brian, Gary, & Eric, 2018;Trott & Naik, 2012). Different from traditional paper-based reading, the rapid development of social reading has a great impact on readers' consumption of texts (Wu & Wu, 2017).…”
Section: Introductionmentioning
confidence: 99%